Hierarki Hukum dan Hukum Perbankan Syariah Indonesia - Rozy, Vikri; Nurnasrina, Nurnasrina; Syahpawi, Syahpawi (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
Research Objective: This study aims to discuss the hierarchy of law in Islamic banking. A recurring issue is the effectiveness of the legal hierarchy in the framework of Islamic banking, which sometimes does not function significantly, consequently impacting the effectiveness of the law in Islamic banking. An examination of the issues regarding Islamic banking regulations becomes a discourse that requires finding solutions. Method: The research employs library research, which is a method of acquiring data and information by utilizing available library resources such as books, journals, documents, historical records, or pure literature related to the research object to gain a deeper understanding of the hierarchy of law in Islamic banking using a thematic approach.Results: The findings of this research reveal that Islamic banking in Indonesia is grounded in two legal foundations, namely Islamic law and positive law, supported by government regulations. The hierarchy of law in Islamic banking comprises various forms, including laws, Bank Indonesia regulations, Financial Services Authority (OJK) regulations, and National Sharia Council (DSN) fatwas.